2018
DOI: 10.1186/s12942-018-0123-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors related with public open space use among adolescents: a study using GPS and accelerometers

Abstract: BackgroundLow physical activity levels and high levels of sedentary time among adolescents call for population wide interventions. Public open spaces can be important locations for adolescents’ physical activity. This study aimed to describe the prevalence, frequency and context of public open space visitation and to gain insight into the individual, social and physical environmental factors associated with public open space use among 12- to 16-year-old Flemish (Belgian) adolescents.MethodsGlobal positioning s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 80 publications
2
19
0
3
Order By: Relevance
“…Parents also felt that older siblings who engage in more screen time have the potential to be a negative influence on the sedentary behaviours of younger siblings. 61 Children with siblings participate in more active transportation 70 71 and time in open space, such as parks, 72 with few studies reporting no association with sibling status. 73–75 Studies with no association in active transport theorised the age of the sibling as the explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Parents also felt that older siblings who engage in more screen time have the potential to be a negative influence on the sedentary behaviours of younger siblings. 61 Children with siblings participate in more active transportation 70 71 and time in open space, such as parks, 72 with few studies reporting no association with sibling status. 73–75 Studies with no association in active transport theorised the age of the sibling as the explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Park physical features may also play a vital role in encouraging park use or physical activity among residents [65], especially for specific features, e.g., playgrounds [66], water features [67] and vegetation [68]. In contrast, other features, such as litter, vandalism and poor playground surface quality have been shown to have a negative impact on park use [69,70].…”
Section: Factors Affecting Park Usementioning
confidence: 99%
“…Within the domain of active recreation, existing literature has identified the importance of parks for adolescents to accumulate PA [ 14 16 ]. However, previous research has also indicated that low numbers of adolescents are visiting parks [ 17 , 18 ]. It is therefore important to understand which physical and social park characteristics [ 19 ] may attract adolescents to visit and be physically active in parks.…”
Section: Introductionmentioning
confidence: 99%